Eddy Current Non-Destructive Evaluation of Conductive Materials - Ladislav Janousek; Tomas Marek; Daniela Gombarska (Communications - Scientific letters of the University of Zilina, 2006)
Non-destructive methods of material properties evaluation are presented in the paper. The methods are useful especially for increasing the safety of sophisticated and environment threatening facilities and, consequently, for decreasing the operating expenditures of those facilities. The attention is paid mainly to the method that utilises eddy currents induced in the surface layer of conducting samples by means of a small flat coil. The eddy current testing method is theoretically described and results of its particular application are presented in the paper.